E-COMMERCE AS A TECHNOLOGICAL INNOVATION STRATEGY OF ENTREPRENEURS IN BANDUNG TO INCREASE SALES IN DIGITAL ERA - Harnani, Nining; Rudi Suprianto Ahmadi; Nana Suhana; Luthfi Setiadiwibawa (Dinasti Publisher, 2020)
The purpose of this research is to investigate how e-commerce can increase sales volume in the creative food and beverage industries. The data used in this research is quantitative data from the sources; whereas the primary data is gathered through questionnaires, interviews and observations. Furthermore, to complete the data, the author also reviews documents from relevant government agencies, journals, books and other references from the Internet as secondary data. The method used in this research is descriptive verification. The type of research is descriptive verification. The study is conducted to test the effect of e-commerce on sales volume by using simple linear regression. Then to determine the effect, the writers use the formulas of Correlation and Coefficient of Determination. The results show that e-commerce has a significant effect on sales volume by 56%. While the remaining 44% is influenced by other factors outside the focus of this study.